Degradation of microcystin-LR and cylindrospermopsin by continuous flow UV-A photocatalysis over immobilised TiO2. (15th December 2020) - Camacho-Muñoz, Dolores; Fervers, Anne-Sophie; Pestana, Carlos J.; Edwards, Christine; Lawton, Linda A.
Abstract: The increasing presence of freshwater toxins have brought new challenges to preserve water quality due to their potential impact on the environment and human health. Two commonly occurring cyanotoxins, microcystin-LR and cylindrospermopsin, with different physico-chemical properties were used to evaluate the efficiency of photocatalysis using a continuous-flow reactor with immobilized TiO2 on glass tubes and UV-A light. The effect of flow rate and hydrogen peroxide addition on the efficiency of cyanotoxin removal were evaluated. An analysis of the effects on microcystin-LR removal efficiency showed that low flow rates (1 mL/min) and high H2 O2 concentrations (120 mg/L) were needed to provide effective degradation. Up to 27.9% and 39.1% removal of MC-LR and CYN, respectively were achieved by UV-A/TiO2 after a single pass through the reactor. A slight increase of the removal of both cyanotoxins was observed when they were in a mixture (35.5% of MC-LR and 51.3% of CYN). The addition of H2 O2 to the UV/TiO2 system led to an average removal enhancement of 92.6% of MC-LR and of 29.5% of CYN compared to the UV/TiO2 system. Photolysis assisted by H2 O2 degraded MC-LR by up to 77.7%. No significant removal (<10%) was observed by photolysis alone or physical adsorption. This study presents a proof-of-principle that demonstrates the feasibility for this technology to be integrated in large-scale applications. Graphical abstract: Image 1 Highlights: Continuous flow UV photocatalysis with immobilized TiO2 applied to degrade freshwater toxins. UV/TiO2 /H2 O2 is an efficient technology to degrade MC-LR and CYN in continuous flow system. Feasibility study for this technology to be integrated in large-scale applications.